The Reading Corner as literary literacy practice - Souza, Renata Junqueira de [UNESP]; Cosson, Rildo (Editora Univ Federal Parana, Centro Politecnico, 2018)
Due the pedagogical concerns about reader formation, the Literature taught in the first cycle of elementary school usually suffer an inappropriate process of schooling. However, this scene can be changed when one takes the literary literacy approach. The analysis of the Reading Corner as a literary literacy practice in this level of teaching shows that even traditional activities can be turned in an well succeed alternative to the literary reader formation.
Keywords: Literary Reader; Reading Corner; Shared Independent Reading; Literary Literacy; Reader Formation